COMPARATIVE ANALYSIS OF THE IN VITRO EQUIVALENCE OF METERED AEROSOL INHALERS CONDUCTED BY THE NEW GENERATION IMPACTOR - L. A. Trukhacheva; N. V. Gorpinchenko; S. P. Dementyev (Union of pediatricians of Russia, 2012)
Aim. To compare in vitro the aerodynamic particle size distributions of original and generic inhalers, which contain both fluticasone (FP) and salmeterol (SM).Material and methods. The Next Generation Impactor (NGI; Copley Ltd., UK) was used to assess the particle size distribution and aerosol quality of two products to determine the equivalence in the aerosol released from the device. The first formulation was Seretide (SM/FP) 25/250 μg, an original SM/FP fixed combination developed by GlaxoSmithKline. The second formulation tested was Tevacomb 25/250 μg (SM/FP), the generic SM/FP fixed combination produced by Cipla. The mass of FP and SM recovered from each stage of impactor was quantified via high performance liquid chromatography (HPLC). The impactor results were statistically evaluated by log transformation of the single data NGI. Results. Statistically significant differences were seen between the deposition profile of Seretide and Tevacomb obtained using the NGI. Evaluating the single stages results in estimation of nonequivalence for all stages except stage 5 (FP) since their confidence intervals (CI) were out of the range of the tight conventional bioequivalence limits of Ѓ} 15 % (0,85-1,18). Also differences were observed by number of parameters, including the fine particle dose (FPD), emitted dose (ED), mass median aerodynamic diameter (MMAD), and geometric standard deviation (GSD) of SM and FP. Conclusion. These in vitro findings suggest that the particle size distributions of the generic formulation Tevacomb is not equivalent to that of the original product Seretide.